2022
DOI: 10.1111/jipb.13379
|View full text |Cite
|
Sign up to set email alerts
|

CHH methylation of genes associated with fatty acid and jasmonate biosynthesis contributes to cold tolerance in autotetraploids of Poncirus trifoliata

Abstract: Polyploids have elevated stress tolerance, but the underlying mechanisms remain largely elusive. In this study, we showed that naturally occurring tetraploid plants of trifoliate orange (Poncirus trifoliata (L.) Raf.) exhibited enhanced cold tolerance relative to their diploid progenitors. Transcriptome analysis revealed that whole‐genome duplication was associated with higher expression levels of a range of well‐characterized cold stress‐responsive genes. Global DNA methylation profiling demonstrated that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 82 publications
1
5
0
Order By: Relevance
“…Similarly, the decrease in CHH methylation downstream of two crucial JA synthesis genes, PtrLOX3 and PtrAOC2, also led to their upregulation in tetraploids. This pattern suggested that tetraploids, due to more extensive DNA demethylation, synthesized UFAs more effectively and relayed JA signaling more efficiently, mounting a more intense response to cold stress in tetraploids than in diploids [109]. In addition, exposure to stressful environments induced epigenetic alterations that might persist even after the stress has subsided, thus establishing a 'stress memory'.…”
Section: Epigenetic Modification Affects Polyploid-induced Stress Tol...mentioning
confidence: 99%
“…Similarly, the decrease in CHH methylation downstream of two crucial JA synthesis genes, PtrLOX3 and PtrAOC2, also led to their upregulation in tetraploids. This pattern suggested that tetraploids, due to more extensive DNA demethylation, synthesized UFAs more effectively and relayed JA signaling more efficiently, mounting a more intense response to cold stress in tetraploids than in diploids [109]. In addition, exposure to stressful environments induced epigenetic alterations that might persist even after the stress has subsided, thus establishing a 'stress memory'.…”
Section: Epigenetic Modification Affects Polyploid-induced Stress Tol...mentioning
confidence: 99%
“…In a research article, (Li et al, 2022) show that BRAHMA, a chromatin remodeler, recruits a histone deacetylase to modulate root system architecture in response to phosphate starvation in Arabidopsis . (Wang, Zuo, et al, 2022) reveal how global demethylation contributes to the enhanced cold tolerance in the polyploid plant trifoliate orange ( Poncirus trifoliata ) compared with its diploid progenitors. Moreover, the ABA signaling pathway has central functions in stress responses and new reports in this issue reveal how epigenetic regulation interacts with ABA signaling.…”
mentioning
confidence: 99%
“…Moreover, the ABA signaling pathway has central functions in stress responses and new reports in this issue reveal how epigenetic regulation interacts with ABA signaling. (Wang et al, 2022) identify DEMETHYLATION REGULATOR 1 as a regulator of DNA methylation in the nuclear and mitochondrial genomes acting upstream of ROS1 and responding to ABA. In addition, (Tang et al, 2022) reveal how removal of the RNA modification N6‐methyladenosine by an RNA demethylase modulates ABA responses.…”
mentioning
confidence: 99%
See 2 more Smart Citations